Pengaruh Motivasi Kerja dan Kinerja Karyawan terhadap Produktivitas Perusahaan PT. BSA Gresik - Kusnul Yatimah; Is Fadhillah (Jurnal Simki Economic, 2024)
Human resources have an important role in a company so that the company can increase its productivity. Human resource management is influenced by many factors that will affect employee performance. One of the factors that affects employee performance is work motivation. The purpose of this study is to examine the effect of work motivation and employee performance on company productivity at PT. BSA Gresik. This research method uses a quantitative method. Data collection was carried out by distributing questionnaires to 67 respondents obtained based on the number of samples using the slovin formula. Data analysis was carried out using a partial hypothesis test (t-test). The results of this study indicate that work motivation has a significant effect on company productivity at PT. BSA Gresik. Where the work motivation variable (X1) obtained a calculated t value (7.102)> t table (1.667) and a significant value of 0.00 <probability value of 0.05. Employee performance has a significant effect on company productivity at PT. BSA Gresik. Where the performance variable (X2) obtained a calculated t value of (3.391) > t table (1.667) and a significant value of 0.01 < probability value of 0.05.